Resveratrol derivative-rich melinjo (Gnetum gnemon L.) seed extract improves obesity and survival of C57BL/6 mice fed a high-fat diet. Issue 12 (2nd December 2015) - Ikuta, Tomoki; Saito, Shinichiro; Tani, Hiroko; Tatefuji, Tomoki; Hashimoto, Ken
Abstract: Melinjo ( Gnetum gnemon L.) seed extracts (MSEs) are rich in resveratrol dimers (gnemonoside A, C, D, gnetin C), trans -resveratrol, and other resveratrol derivatives. trans -Resveratrol is a widely studied caloric restriction mimetic. In mice fed a high-fat diet (HFD), trans -resveratrol protects against obesity, type 2 diabetes, and premature death. Here, treatment of HFD-fed mice with 2.0% MSE significantly reduced body weight gain ( p  < 0.001), blood insulin ( p  < 0.01), and HOMA-IR ( p  < 0.05) after 8 weeks compared with untreated HFD-fed mice. Additionally, 0.2% MSE treatment of HFD-fed mice significantly improved physiological activity ( p  < 0.05) at 18 months of age and reduced risk of death due to HFD by 25% (hazard ratio = 0.75, p  = 0.036). These data show that MSE can improve several aspects of metabolic syndrome and survival in mice and may have health benefits as a dietary supplement. Graphical abstract: : Resveratrol derivative-rich melinjo ( Gnetum gnemon L.) seed extract improves survival of C57BL/6 mice fed a high-fat diet.